Circular cities: planning for circular development in European cities. Issue 1 (2nd January 2023) - Williams, Jo
ABSTRACT: Circular development could produce more resource efficient, ecologically regenerative and resilient cities. This development pathway offers many ecological, social and economic benefits. However, there are also many challenges to implementation, not least a heavy reliance on the market to transform urban systems of provision. A regulatory and policy framework is essential for a circular transformation, until circular activities become competitive within existing markets. Spatial and land-use planning can offer this framework. This paper provides insight into the circular development process. It discusses the role of planning in delivering circular development, using examples from four European cities. It identifies the tools for delivery and discusses the inherent limitations of using planning tools to deliver a circular transformation.